Competition between intermediate plaquette phases in SrCu2(BO3)(2) under pressure - Boos, Carolin; Crone, S. P. G.; Niesen, I. A.; Corboz, P.; Schmidt, Kai Phillip; Mila, F. (Physical Review B, 2019)
Building on the growing evidence based on NMR, magnetization, neutron scattering, electron spin resonance, and specific heat that, under pressure, SrCu2(BO3)(2) has an intermediate phase between the dimer and the Neel phase, we study the competition between two candidate phases in the context of a minimal model that includes two types of intra- and interdimer interactions without enlarging the unit cell. We show that the empty plaquette phase of the Shastry-Sutherland model is quickly replaced by a quasi-one-dimensional full plaquette phase when intra- and/or interdimer couplings take different values, and that this full plaquette phase is in much better agreement with available experimental data than the empty plaquette one.
CRIS-Team WoS Importer:2019-11-15